Meretas Perilaku Bullying : Toxic Relantionship di Sekolah: Bentuk toxic yang paling sering dilakukan adalah body shaming, menjadikan penampilan fisik sebagai bahan candaan. - Fauzi, Taty; Ferdian, Leo; Indra Utama, Bayu; Nurbaiti (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2023)
The development of technology in the last 15 years has developed rapidly, communication is no longer bound by time and space. This phenomenon makes relationships between individuals and groups almost limitless. In line with these developments, there is often unethical behavior that even violates norms - to be fatal to the growth and development of students. The Community Service Team is carried out collaboratively with 3 lecturers in Palembang City, the main focus is to provide information so that students understand every behavior or action carried out categorized as bullying or violence. The goal is that they can be careful in communicating either orally or through media (Instagram, watchApp). The methods provided through lectures, questions and answers and video playbacks, pictures about toxic forms and their impact on psychology.